MIDLIFE CRISIS IN MEN AND WOMEN: SIMILARITIES AND DIFFERENCES - Soni Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
Research on the anatomical differences that exist between the male and female brains has progressed significantly during the last several decades. The one conclusion that remains constant across all studies is that males have bigger brains than women do (postmortem: in vivo imaging: Studies that follow subjects over time have shown, throughout time, that there are variations in the patterns of brain development that occur between the sexes in children and adolescents. For instance, a longitudinal pediatric neuroimaging research conducted 829 scans on 387 participants ranging in age from 3 to 27 years old. The participants were all children. According to the findings of the study, the peak of total brain volume occurred earlier in girls than in boys.